Some Psychological Implications of Black Struggle. Issue 1 (1st June 2021) - Leach, Colin Wayne; Teixeira, Cátia P.
Abstract : Yet another long, hot summer in 2020 brought to the broader consciousness—in the US and well beyond—what Black folks have known for centuries about the ways in which racial hegemony relies on the acute violence of a police knee on a prone neck and the chronic violence of prisons, prefects, and (public housing) projects (for discussions, see Bulhan 1985; Omi and Winant 2014; Sidanius and Pratto 1999). In their commentary, AK Thompson makes too many important points for us to address in this brief commentary. Thus, as research psychologists with a transdisciplinary social-behavioral approach to protest, resistance, and societal change, we focus on what we see as Thompson's most psychologically oriented theses: II, III, V, and VI. In sum, we see Thompson as arguing that social movements necessarily include a (more or less latent) threat of violence (II) and that this violence is noticed and suppressed because it challenges (III) the logic (economic, political, and cultural), the ethics, and the formalization (legal, political, and institutional) of racial hegemony (V). In addition, we take Thompson to argue that Black freedom struggles are, and have always been, flexible in means and aims (VI), adjusting strategically to the multifaceted dynamics of oppression and resistance.